Students' Attitudes towards Computer-Mediated Audio Feedback - Giridharan, Beena; Gopalai, Alpha; Krishnan, Murali; Lau, Crystal (Office of Teaching and Learning, Curtin University Sarawak, Malaysia, 2013)
This paper reports from an ongoing study investigating students’ attitudes towards computer mediated audio feedback. There is adequate research evidence to support the notion that feedback affects student learning positively, yet students often express dissatisfaction on the timeliness and quality of feedback received on their academic assignments. Additionally surveys conducted at universities show that satisfaction with feedback is generally rated lower than other aspects of learning experiences (Tucker & Pegden, 2010). The study focuses on understanding students’ perceptions towards computer mediated audio feedback on assignments using Audacity software that allows lecturers to provide automated personalised audio feedback to students on their written assignments through electronic audio files. Literature on studies conducted to examine how students view audio feedback or use them effectively for advancing learning is scarce. In this project ‘effective feedback’ refers to information provided to students regarding their performance in assignments or assessments that are detailed and specific, and focuses on improving their learning.The paper reports on experiences from three units that employed the use of audacity in the feedback provided to students on assignments. Initial reports from a unit reported some adjustment challenges in student acceptance of the feedback format which decreased progressively over the 12 week semester. However, it was observed that the quality of students’ submission improved as the semester progressed. This could be attributed to feedback regarding past assessments being provided in a timely and concise manner, as each student received personalized feedback. Students demonstrated a clearer understanding of the learning outcomes and criteria for the assessments. In another unit, students responded positively to the use of audio feedback stating that it was value adding to their learning. It was also perceived that the notion of audio feedback is well intentioned and may assist in reducing the distance in the student –teacher relationship.